Diplomatic training and Sovereignty: Insights from Non-Western States - I. V. Kiseleva; I. S. Khludov; A. I. Gladysheva; A. K. Adrianov; V. A. Perunov; S. A. Davydov (Международная аналитика, 2025)
The paper examines how the sovereignty of national diplomatic training schools in the Global South influences their standing within the regional subsystems. The study is relevant in light of the growing clout of non-Western countries in global politics and economy, as well as their ever-increasing significance for Russia. We focus on countries that seek to pursue especially proactive foreign policies: Egypt, Iran, Saudi Arabia, and Turkey in the Middle East; Nigeria, Ethiopia, and South Africa in Sub-Saharan Africa; Brazil, Cuba, and Mexico in Latin America. The authors employ a cross- regional comparative analysis of diplomatic training there, supplemented by a biographical method that traces the career trajectories of prominent foreign ministry officials. Our research rests on selected post-structuralist, post-colonial, neo-Marxist, and post-critical approaches to sovereignty in states deemed peripheral or semi-peripheral. Additionally, we take stock of various approaches to diplomacy as an institution and further conceptualize how the indigenous diplomatic practices of individual states shape their role in the region. Our findings partly support the hypothesis that higher levels of sovereignty (sophistication) in national diplomatic training schools help these states to set the (sub)regional agenda. However, high levels of sovereignty in diplomatic training, as opposed to sophistication, do not necessarily translate into a country’s ability to set the regional agenda.